Green emission of tellurite based glass containing erbium oxide nanoparticles - Abd Azis, Muhammad Noorazlan; Mohamed Kamari, Halimah; Omar Baki, Sharudin; Wan Yusoff, Wan Mohamad Daud (Hindawi Publishing Corporation, 2015)
Investigation on green emission and spectral intensity of tellurite based glass containing erbium oxide NPs is one of the crucial issues. Tellurite based glass containing erbium oxide NPs with the composition of {[(TeO2)0.70(B2O3)0.30]0.7(ZnO)0.3}0.95(Er2O3)0.05 has been prepared by using conventional melt-quenching method. The structural and optical properties of the glass sample were characterized by using XRD, FTIR, UV-Vis absorption, and PL spectroscopy. The amorphous structural arrangement was proved through XRD method. The formation of TeO3 and BO3 units was revealed by FTIR analysis. Five transition states of excitation were shown in UV-Vis spectra which arise from the ground state 4I15/2 to the excited states 4G11/2 + 2H9/2 + 4F5/2 + 4F7/2 + 2H11/2 + 4S3/2 + 4F9/2 + 4I9/2 + 4I11/2. The intensity parameters Ωt (t=2, 4, 6) are calculated and follow the trend of Ω2 > Ω4 > Ω6. Broad green emission at 559 nm under 385 nm excitation was obtained.